From Static To Sentient: Designing Emotionally Responsive Interfaces Using Affective Computing For UX Enhancement - Prasetya, Dedy; Utami, Ika Inayati Budi; Pertiwi, Silvi (International Journal of Graphic Design, 2025)
Abstract This study explores the integration of artificial intelligence (AI), particularly generative and affective computing, into user experience (UX) and creative industry workflows. It investigates how recent advancements in multimodal AI, user interface (UI) design, and emotion recognition can enhance personalization, user satisfaction, and design efficiency. Drawing from cross-disciplinary literature, the paper highlights the transformative potential of tools such as DALL·E, Midjourney, and Adobe Firefly in supporting ideation and prototyping, while also addressing concerns about emotional authenticity, ethical transparency, and cultural sensitivity. Findings suggest that AI-driven UX innovations must be grounded in human-centered design to retain user agency and trust, especially in emotionally sensitive contexts. The study emphasizes the role of affective computing in enabling adaptive digital environments through real-time emotion recognition. However, limitations related to the generalizability of findings, lack of empirical testing, and rapid technological evolution are acknowledged. Future research directions include empirical validation of AI-UX frameworks, cross-cultural testing, and interdisciplinary collaboration to ensure ethical, inclusive, and emotionally intelligent design systems. Overall, the study contributes to a growing discourse on the responsible integration of AI in UX, proposing that technology should act as a co-creative partner rather than a replacement for human creativity and empathy.